Identification and characterization of glycoproteins during oil palm somatic embryogenesis - Aroonluk, Suvichark; Roytrakul, Sittiruk; Yingchutrakul, Yodying; Kittisenachai, Suthathip; Jantasuriyarat, Chatchawan (Agriculture and Natural Resources, 2018)
The objective of this experiment was to characterize differentially expressed glycoprotein in a somatic embryogenesis process during oil palm tissue culture. Embryogenic callus in the somatic embryo acquisition stages (globular, torpedo and cotyledonary) and oil palm plantlets were collected to extract total protein and isolated glycoprotein using a concanavalin A N-linked affinity column. Tryptic glycoproteins were isolated using nano-liquid chromatography-tandem mass spectrometry. In total, 383 glycoproteins were identified and analyzed. The percentages of existence of glycoprotein were observed, from highest to lowest amounts, in the metabolic process, binding and nuclear components, respectively. Different glycoproteins were involved in membrane trafficking machinery, signaling to stress and in hormonal and environmental response for plant growth and development. PREDICTED: protein TIC 40, chloroplastic-like was expressed in the globular, torpedo and plantlet stages. The protein can be further developed into a glycoprotein biomarker, as a biological indicator of the somatic embryo maturation stage. This study should assist deeper understanding of the important role of glycoprotein specificity in somatic embryogenesis that controls plant cell response and growth development during oil palm tissue culture.